IMPLEMENTASI KEBIJAKAN PENGADAAN BARANG DAN JASA SECARA ELEKTRONIK PADA BAGIAN PENGADAAN BARANG DAN JASA SEKRETARIAT DAERAH KABUPATEN PARIGI MOUTONG - Nuryadin Gunardi; Hj. Nuraisyah; M. Nur Alamsyah; Nuraisyah (CV. ALIM'SPUBLISHING, 2024)
The objective of this study is to analyze the implementation of electronic goods and services procurement policies in the Procurement Division of the Regional Secretariat of Parigi Moutong Regency. This research is a qualitative study with a descriptive method. Data collection techniques were conducted through observation, interviews, and triangulation. The data were analyzed using the Miles and Huberman method, which involves data reduction, data presentation, and conclusion drawing and verification. The model used in this research is the one developed by Edward III, known as A Model of the Policy Implementation Process. This model identifies four variables that influence the relationship between policy and performance: communication, resources, disposition, and bureaucratic structure. The results of the study indicate that the implementation of electronic goods and services procurement in Parigi Moutong Regency has not been optimal. The communication aspect has been functioning well with coordination and socialization in place, but the aspects of resources, disposition, and bureaucratic structure are still suboptimal. The main obstacles are the limited number of human resources with IT expertise and inadequate infrastructure. Disposition is not yet optimal as many OPDs (Regional Government Organizations) still use manual methods, and the bureaucratic structure is not fully supportive due to the lack of clear technical guidelines or SOPs. Based on the research findings, it can be concluded that the implementation of electronic goods and services procurement in Parigi Moutong Regency has not been optimal. While the communication aspect is functioning well, the aspects of resources, disposition, and bureaucratic structure need improvement to achieve better performance.